Exploring the safety of the sustainable toxicity testing in zebrafish and brine shrimp using nanoemulsions formulated from fish byproducts and lemon oil - Hendawy, Amira Ayman; Elgharbawy, Amal A M; Mohd Noor, Najihah; Al-Saari, Nurhidayu; Azmi, Nor Azrini Nadiha; Mohd Salleh, Hamzah (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Nanoemulsions, characterized by their nanosized particles ranging from 20 to 200 nm, are effective carriers for drug molecules. Our novel oil-in-water nanoemulsion, NE-FLO™, formulated from lemon and fish byproduct oils, demonstrates promising antioxidant and anti-inflammatory activities, with initial studies indicating nontoxicity to normal skin cells. This study investigated the safety of NE-FLO™ using brine shrimp (Artemia salina) and zebrafish (Danio rerio) models, focusing on concentration-dependent effects and LC50 values. At lower concentrations (0.1 mg·L−1, 0.01 mg·L−1, and 0.001 mg·L−1), NE-FLO™ showed minimal toxicity without adverse effects. However, at 1 mg·L−1, reduced survival rates indicate potential toxicity. Specifically, this concentration also induces altered swimming behaviors in zebrafish. LC50 values are 8.7474 mg·L−1 for brine shrimp and 0.316 mg·L−1 for adult zebrafish. These results underscore the necessity for further detailed investigations into NE-FLO™, balancing its therapeutic benefits with potential toxicity risks. This study emphasizes the importance of optimizing nanoemulsion formulations from fish oil and conducting comprehensive safety assessments to meet regulatory standards.